Transforming teaching practices: Enhancing ICT-pedagogy integration through curriculum innovations in teacher education of Bangladesh - Islam, Muhammad Monirul; Rahman, Mahbuba; Rabbi, Md. Fajlay (Univeritas Papua, 2023)
The use of ICT in teaching and learning processes at all levels was highlighted in Bangladesh's educational policy. According to studies, there are not enough secondary-level instructors in Bangladesh who are proficient in using digital technologies for instruction. The purpose of this research was to explore options for updating the teacher education curriculum by filling up any gaps found in the development of ICT-Pedagogy integration abilities. In this study, the TPACK framework was utilized to pinpoint curriculum gaps, and a mixed-method approach was used to achieve the study's goals. The curriculum was first examined to find any deficiencies, and then key informant interviews looked at potential updates to the curriculum that might fill those gaps. The study discovered a lack of proper teaching-learning methods and assessment, as well as clear objectives and topics on ICT and pedagogy integration. The study promoted a few approaches for teacher skill upgrades to improve their ability to teach with ICT.